Eksistensi Tradisi Sentek Dulang Bao Masjid sebagai Wadah Membangun Ukhuwah Islamiyah di Masyarakat Sebeok Kecamatan Orong Telu, Kabupaten Sumbawa, Provinsi NTB - Andi Tamrin; Masiratul Helmi; Muliadi Muliadi; Viny Asri Supratiwi; Shofia Juniarti; Baiq Hidayatunnisa; Hidayati Hidayati; Gaoz Rozi Fahraini (BADAN PENERBIT STIEPARI PRESS, 2025)
The Sentek Dulang Bao Masjid tradition is a cultural heritage of the Sebeok community that has been preserved across generations as a unifying medium and a means of fostering Ukhuwah Islamiyah (Islamic brotherhood). This practice is carried out during significant occasions such as Islamic holidays, weddings, and thanksgiving ceremonies, serving as a platform for social interaction among residents. Through the ritual of sharing food on a dulang (large tray) followed by communal prayers, this tradition manifests the values of togetherness and brotherhood in Islam. Over time, Sentek Dulang Bao Masjid has evolved beyond a religious ritual to function as a mechanism for strengthening social cohesion amidst the heterogeneity of Sebeok Village society. This study reveals how the existence of the Sentek Dulang Bao Masjid tradition plays a strategic role in building and reinforcing Ukhuwah Islamiyah. Employing an ethnographic approach with participatory observation and in-depth interviews, the research found that this tradition serves as an effective communication space that facilitates conflict resolution and fosters mutual understanding among community members. The preparation and implementation of this ritual involve all elements of society, regardless of social status, reflecting the egalitarian values inherent in Islamic teachings. Despite facing challenges from modernization and social change, the people of Sebeok Village continue to uphold the essence of this tradition through adaptations that do not diminish its fundamental values. The findings indicate that the sustainability of the Sentek Dulang Bao Masjid tradition as a vehicle for developing Ukhuwah Islamiyah is supported by three main pillars: the endorsement of religious and customary leaders, the active participation of the younger generation, and the integration of traditional values into informal education within the community. This tradition serves as a bridge linking Islamic values with local wisdom, thus creating enduring social harmony. Consequently, Sentek Dulang Bao Masjid is not only a cultural identity of the Sebeok community but also an effective instrument for strengthening Islamic unity and brotherhood in the contemporary era.